Artificial Neural Networks Pengenalan Pola Pasword Angka Menggunakan Metode Heteroassociative Memory - Silvilestari, S ` (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Every important data must be kept confidential so that it is not misused by people who do not have the right to access the data. Data security can be used using the Heteroassociative Memory Method. The Heteroassociative Method is used to collect data from each combination and then become a complex system so that it can be mapped into a system with the resulting values. The problem that often occurs is data security which is often stolen by unauthorized people because the data security key in the form of a numeric password can be hacked easily. The aim of the research is to help maintain data confidentiality by providing a password pattern lock on the system so that it is difficult for data thieves to enter the system. How the Heteroassociative Memory Method works uses weight values determined in such a way that the network can store groupings of patterns. Each group is a pair of vectors. The research results of 8 number patterns with input 1111 0110 1100 1000 0011 1100 1111 1011 produce 4 patterns that match the target, namely pattern 1 to pattern 4 and 4. Patterns that do not match the target, namely pattern 5 to pattern 8. Recognition of number patterns depends on the input target. .